Tim Rushton's Requiem for the Royal Danish Ballet (Recent Reviews) - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2006)
PALABRAS CLAVE: Royal Danish Ballet, Tim Rushton, Requiem.
Dentro del apartado: "Dance Now: Recent reviews"